Selection and culture condition optimisation for amylase biosynthesis of marine fungal strains isolated from Nha Trang Bay and Van Phong Bay, Khanh Hoa province - Thuỷ, Phạm Thu; Sở, Đinh Thị; Duy, Nguyễn Văn (Hue University Journal of Science: Natural Science, 2020)
Marine fungi play an important role in marine ecosystems and provide numerous valuable industrial products. This study screens for amylase-producing marine fungi strains and studies the appropriate culture conditions to obtain enzymes. From 160 isolated strains, all yeast strains do not exhibit amylase activity (0/112 strains), while the molds display amylase activity with a high rate at 70.8% (34/48 strains). Among these molds, the DM12M strain has the highest amylase activity (13.0 U/mL). Suitable culture conditions for amylase production of this strain are the modified Czapek–Dox medium supplemented with 1% soluble starch, 0.3% NaNO3, 0.5% NaCl, and 5 days incubation at pH 6.0 and 30 °C. Under these conditions, the amylase activity of the DM12M strain reaches 59.0 U/mL, approximately 4.5 times higher than that under pre-optimalization conditions. The DM12M strain has the ITS1-5.8S-ITS2 nucleotide sequence of 99.8–100% similarity to the strains of Aspergillus aculeatus; this reveals that it may belong to this species. The research provides scientific data on the factors affecting the ability of the marine fungi to produce extracellular amylase and opens up their potential for industrial application.